Pengaruh Kompensasi , Kedisiplinan Dan Teamwork Terhadap Motivasi Kerja Pegawai Perangkat Desa Di Desa Padangsari Kecamatan Majenang Kabupaten Cilacap (Studi Kasus Pada Kantor Balai Desa Padangsari Tahun 2022-2023) - Aulia Firda; Saur Panjaitan (Universitas Dian Nuswantoro, 2022)
The purpose of this research is to find out what factors influence the provision of compensation, discipline, and teamwork on the work motivation of village officials in Padangsari village, Majenang sub-district, Cilacap district. Observing what influences the provision of compensation to apparatus employees in the village of Padangsari sub-district, Cilacap district. This research uses quantitative research methods. This type of research is to use a quantitative research type, the population of village officials and a sample of 97 employees. This study uses Structural Equation Modeling (SEM) analysis to determine how much independent influence the dependent variable has through the intervening variables using the Lisrel 8.8 program. Based on the results of research in the District, it is known that there are 5 factors that influence the provision of compensation to employees, namely: education, workload and responsibilities, position, rank or class, and work performance. The results of the study show that there are differences in the awarding of Rank Compensation (Group) which is also a factor to consider in increasing the compensation received by a person.